Tourism to Socio Culture and Economy of Community in Panusupan Purbalingga - Agung Edi Rustanto; Donny Oktavian Syah (Faculty of Economics and Business, University of Pasundan, 2018)
The aim of this research is to study the impact of tourism development to socio-culture and economy of community in Panusupan village, Rembang, Purbalingga. The research, which was conducted in the end of 2016, uses descriptive quantitative method. Sampling technique used is random sampling technique. Survey was conducted to 100 respondents. The data are analyzied by using simple linear regression The result of this research shows that partially tourism development gives impact 31.5% to socio culture, 45.6% to socio economy whereas the impact of socio culture to socio economy is 32.0% .